A evoluç\~ao do Programa de Aquisiç\~ao de Alimentos (PAA): Uma análise da sua trajetória de implementaç\~ao, benefícios e desafios - Gabriela Perin; Ana Flávia Cordeiro S. de Almeida; Paulo Asafe Campos Spínola; Antônio Fernando Costa Pella; Regina Helena Rosa Sambuichi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– Created in 2003 with the objective of promoting family farming and combating food insecurity of people in vulnerable situations, the Food Acquisition Program (PAA) has been an important marketing channel for small rural producers and a relevant way of promoting access to healthy food public policy. Throughout its trajectory, several normative and institutional changes were made in order to improve its implementation. This work aims to analyze the evolution of the implementation of PAA along its trajectory in the period 2003-2019, seeking to understand how changes in its regulations and execution history may have influenced the results of the program in relation to its main benefits and challenges. The method used in this study included document analysis, systematic literature review and content analysis. The document analysis revealed three main periods of PAA's implementation. The initial period (2003-2008) was of learning and organizing processes both at the managerial and local level. The intermediate period (2009-2013) had as main characteristics the strengthening of the program, marked by the role of the National Supply Company (Conab), the emergence of another implementation modality (by Adhesion Term), operated by the Ministry of Social Development and Fight against Hunger (MDS) and, finally, the Agro-Fantasma Operation, which caused an abrupt drop in program operations at the end of this period. In the most recent period (2014- 2019), after a slight initial resumption of resources, there was a continuous reduction in the amounts invested in the PAA, reaching the end of the period at the lowest levels in its history. Although there was an effort to redesign its management to reduce bureaucracy and facilitate access, a change in the government's political and institutional agenda had a strong impact on policies for family farming, strongly affecting the program, which in 2019 reached the lowest level of execution of resources in its history The studies raised in the systematic review showed that, throughout its trajectory, the PAA promoted economic, social and environmental gains. It benefited the producer by increasing their income and allowing them to purchase durable goods. In the social sphere, this Program provided diverse and quality food from local production and promoted the recognition and appreciation of family farming, which reflected in the increased self-esteem and autonomy of the producer families. As for the gains in the environmental perspective, the PAA promoted the diversification of cultures, as well as adherence to good production practices. However, the significant reduction in the amounts invested in recent years has reflected in the increase of the challenges for the program, also indicating the possible decrease in some benefits. Recently, in 2021, PAA was replaced by Programa Alimenta Brasil, created along the lines of the previous program. Thus, it is recommended to increase the resources allocated to PAA's actions, and that the regulation of the new program rescues all the original purposes and modalities of PAA, in order to maintain and maximize its potential to generate benefits.
Keywords: Q18; 330; family farming; public policies; food and nutrition security